Human Wharton’s Jelly Mesenchymal Stromal Cell-Derived Small Extracellular Vesicles Drive Oligodendroglial Maturation by Restraining MAPK/ERK and Notch Signaling Pathways - Joerger-Messerli, Marianne S.; Thomi, Gierin; Haesler, Valérie; Keller, Irene; Renz, Patricia; Surbek, Daniel V.; Schoeberlein, Andreina (Frontiers in Cell and Developmental Biology, 2021)
Peripartum cerebral hypoxia and ischemia, and intrauterine infection and inflammation, are detrimental for the precursor cells of the myelin-forming oligodendrocytes in the prematurely newborn, potentially leading to white matter injury (WMI) with longterm neurodevelopmental sequelae. Previous data show that hypomyelination observed in WMI is caused by arrested oligodendroglial maturation rather than oligodendrocyte-specific cell death. In a rat model of premature WMI, we have recently shown that small extracellular vesicles (sEV) derived from Wharton’s jelly mesenchymal stromal cells (WJ-MSC) protect from myelination deficits. Thus, we hypothesized that sEV derived from WJ-MSC directly promote oligodendroglial maturation in oligodendrocyte precursor cells. To test this assumption, sEV were isolated from culture supernatants of human WJ-MSC by ultracentrifugation and co-cultured with the human immortalized oligodendrocyte precursor cell line MO3.13. As many regulatory functions in WMI have been ascribed to microRNA (miR) and as sEV are carriers of functional miR which can be delivered to target cells, we characterized and quantified the miR content of WJ-MSC-derived sEV by next generation sequencing. We found that WJ-MSC-derived sEV co-localized with MO3.13 cells within 4 hours. After five days of co-culture, the expression of myelin basic protein (MBP), a marker for mature oligodendrocytes, was significantly increased, while the oligodendrocyte precursor marker platelet-derived growth factor alpha (PDGFRα) was decreased. Notch and MAPK/ERK pathways known to inhibit oligodendrocyte maturation and differentiation were significantly reduced. The pathway enrichment analysis showed that the miR present in WJ-MSC-derived sEV target genes having key roles in the MAPK pathway. Our data strongly suggest that sEV from WJ-MSC directly drive the maturation of oligodendrocyte precursor cells by repressing Notch and MAPK/ERK signaling.